GAMBARAN KECEMASAN PASIEN SAAT MENJALANI PROSEDUR EKSTRAKSI GIGI SAMBIL MENDENGARKAN MUSIK MOZART DI PUSKESMAS - Tangkere, Harlye; Opod, Hendry; Supit, Aurelia (Universitas Sam Ratulangi, 2013)
Abstract: Tooth extraction is one of the dental treatment done in Community Health Center. Tooth extraction frequently can create anxiety and become a problem if it hamper the performance of the dentist. Various methods have already been done to overcome anxiety, such as listening to classical music, one of the classical music used is Mozart. The purpose of this research is to get an overview of patientâ€™s anxiety when undergoing tooth extraction while listening to the music of Mozart in Community Health Center. This research used descriptive sampling method. The sample consist of 30 adults with 17-65 age, grouped by 18 people who have experienced tooth extraction and 12 people who have not. The data were collected by physical examination and Visual Analogue Scale (VAS) before and after listening to the music of Mozart during extraction procedure. The result showed that those who have not experienced tooth extraction before, 50% of that group had reduction in anxiety according to blood pressure measurement, 8.33% of the group in blood pulse measurement were decreased and 16.67% of the group in respiration measurement, 16.67% of the group in the VAS measurement showed a decrease in anxiety from uncomfortable to mild, 75% from mild to no pain. In the group which have experienced tooth extraction procedure before, 16.67% of the group increased anxiety in blood pressure measurement, there were no reduction in blood pulse measurement, and decreased 11.11% of the group in respiration measurement, according to VAS 22.22% of this group showed that their anxiety decreased from uncomfortable to mild, and 55.56% from mild to no pain. Keywords: extraction procedure, anxiety, Mozart music.Â Â Abstrak: Tindakan ekstraksi gigi merupakan salah satu jenis perawatan gigi yang dilaksanakan di Poli Gigi dan Mulut Puskesmas. Prosedur ekstraksi gigi seringkali menjadi pencetus kecemasan pasien dan dapat menjadi penghambat kinerja dokter gigi. Berbagai metode telah dilakukan untuk mengatasi kecemasan termasuk penggunaan musik klasik, dan salah satu musik klasik yang sering digunakan adalah musik ciptaan Mozart. Penelitian ini dilakukan untuk melihat gambaran kecemasan pasien saat menjalani prosedur ekstraksi gigi sambil mendengarkan musik Mozart di Puskesmas. Penelitian ini adalah deskriptif dengan menggunakan metode pengambilan sampel purposif. Jumlah sampel 30 orang dewasa berusia 17-63 tahun yang terdiri dari 18 orang pernah dan 12 orang belum pernah menjalani prosedur ekstraksi gigi sebelumnya. Data diambil berdasarkan pemeriksaan fisik dan Visual Analogue Scale (VAS) sebelum dan sesudah mendengarkan musik Mozart selama prosedur ekstraksi gigi. Hasil dari kelompok yang belum pernah menjalani ekstraksi gigi, terjadi penurunan kecemasan sejumlah 50% pasien pada pengukuran tekanan darah, sejumlah 8.33% pasien pada pengukuran nadi dan sejumlah 16.67% pasien pada pemeriksaan respirasi, sejumlah 16.67% pasien pada pemeriksaan VAS terjadi penurunan kecemasan dari rasa sakit yang membuat tidak nyaman ke rasa sakit ringan, sejumlah 75% pasien dari rasa sakit ringan ke tidak ada rasa sakit. Bagi kelompok yang pernah menjalani prosedur ekstraksi gigi sejumlah 16.67% pasien mengalami kenaikan kecemasan pada pengukuran tekanan darah, pada pengukuran nadi tidak ada pasien yang mengalami kecemasan, sejumlah 11.11% pasien mengalami penurunan kecemasan pada pengukuran respirasi, sejumlah 22.22% pasien pada pemeriksaan VAS turun dari rasa sakit yang membuat tidak nyaman ke rasa sakit ringan dan sejumlah 55.56% pasien dari rasa sakit ringan ke tidak ada rasa sakit.Kata kunci: Prosedur ekstraksi gigi, kecemasan, musik Mozart.